Edukasi dan Pelatihan Pijat Oksitosin bagi Ibu Menyusui - Heldayati; Prihatiningsih; Sudarni; Srihastuti; Riki Liliyanti; Radiah; Kartika Sari (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2025)
Oxytocin massage is a non-pharmacological method proven effective in stimulating the production of oxytocin hormone, which plays a crucial role in breast milk (ASI) let-down. However, the lack of public knowledge regarding this technique remains a barrier to achieving successful exclusive breastfeeding. This community service program aimed to improve postpartum mothers' knowledge and skills in performing oxytocin massage through structured education, demonstration, and hands-on training. The activity was held on May 28, 2025, at the Integrated Maternity Room of RSUD dr. H. Jusuf SK, Tarakan City, with 12 participants. Methods included a pretest, educational session, live demonstration of oxytocin massage, and posttest. Evaluation results showed a significant increase in participants’ knowledge initially, 66.7% had poor understanding, which improved to 100% with good knowledge after the training. This program demonstrates that oxytocin massage education and training can be an effective intervention in supporting breastfeeding practices and enhancing the success rate of exclusive breastfeeding in the community. Among 12 participants, 66.7% had low knowledge of oxytocin massage before the training. After the session, 100% showed improved knowledge categorized as good. Participants also demonstrated correct massage techniques and actively engaged in the activity. Conclusion: The oxytocin massage education and training program effectively improved postpartum mothers’ knowledge and skills in supporting exclusive breastfeeding. This activity serves as a successful promotive and preventive approach in communit based midwifery care. Abstrak Pijat oksitosin merupakan metode non- farmakologis yang efektif dalam merangsang produksi hormon oksitosin, yang berperan penting dalam pengeluaran Air Susu Ibu (ASI). Namun, kurangnya pemahaman masyarakat mengenai teknik ini menjadi salah satu hambatan dalam pencapaian keberhasilan ASI eksklusif. Program pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan dan keterampilan ibu nifas dalam melakukan pijat oksitosin melalui penyuluhan, demonstrasi, dan pelatihan langsung. Kegiatan dilaksanakan pada tanggal 28 Mei 2025 di Ruang Kebidanan Terpadu RSUD dr. H. Jusuf SK, Kota Tarakan, dan diikuti oleh 12 peserta. Metode yang digunakan meliputi pretest, penyampaian materi, demonstrasi pijat oksitosin, serta posttest. Hasil evaluasi menunjukkan peningkatan signifikan pengetahuan peserta, di mana seluruh responden yang awalnya memiliki tingkat pengetahuan kurang (66,7%) mengalami peningkatan menjadi 100% berpengetahuan baik setelah pelatihan. Dari 12 peserta, 66,7% memiliki pengetahuan kurang tentang pijat oksitosin sebelum pelatihan. Setelah penyuluhan dan demonstrasi, 100% peserta menunjukkan peningkatan pengetahuan menjadi kategori baik. Selain itu, peserta mampu mempraktikkan teknik pijat dengan benar dan antusias mengikuti kegiatan. Program edukasi dan pelatihan pijat oksitosin berhasil meningkatkan pengetahuan dan keterampilan ibu nifas dalam mendukung keberhasilan ASI eksklusif. Kegiatan ini efektif sebagai upaya promotif dan preventif dalam pelayanan kebidanan.